О некоторых свойствах ортогональных по площади полиномов в областях комплексной плоскости. I - Абдуллаев, Ф.Г. (Український математичний журнал, 2000)
Знайдено умови інтерференції особливостей ваги та контуру для ортогональних за площею області поліномів. Отримано нові оцінки швидкості зростання цих поліномів, які залежать від особливостей ваги та контуру. We establish conditions for the interference of singularities of a weight function and a contour for orthogonal polynomials over the area of a domain. We obtain new estimates for the rate of growth of these polynomials, which depend on the singularities of the weight function and the contour.